2019
DOI: 10.24953/turkjped.2019.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Clinical experiences in Turkish paediatric patients with chronic recurrent multifocal osteomyelitis

Abstract: Chronic recurrent multifocal osteomyelitis (CRMO) is a clinical entity which occurs mainly in children and adolescents with recurrent episodes of pain occurring over several years. Cause and physiopathology of disease is still uncertain. We aim to assess clinical characteristics and treatment options, need and response to anti-inflammatory therapies in children diagnosed chronic recurrent multifocal osteomyelitis Demographic data and clinical features of seventeen children diagnosed with CRMO in 2 pediatric rh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 18 publications
2
21
1
Order By: Relevance
“…Sözeri et al 14 reported 17 patients with CNO in their study, which included the second-largest cohort from Turkey after the present study. Their retrospective study included the demographic data and clinical features of 17 children diagnosed with CRMO in two pediatric rheumatology centers.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Sözeri et al 14 reported 17 patients with CNO in their study, which included the second-largest cohort from Turkey after the present study. Their retrospective study included the demographic data and clinical features of 17 children diagnosed with CRMO in two pediatric rheumatology centers.…”
Section: Discussionmentioning
confidence: 80%
“…2 It may be speculated that MEFV mutations, mainly exon 10, may have an inflammatory stimulation of bones with CNO, and additional colchicine treatment is helpful in the disease control. Sözeri et al 14 detected MEFV gene mutations in four patients in whom severity of clinical features reduced with colchicine therapy. Soylemezoglu et al 24 also found a much higher FMF prevalence (14.8%) than expected in the Turkish population (14.8%).…”
Section: Discussionmentioning
confidence: 99%
“…In CNO, the peak onset age was 7-12 years and commonly female predominance was reported [2,11]. The peak onset of CNO in studies from Turkey was between 9 and 10.2 years, and a male predominance was observed in 2 studies [12][13][14]. Likewise, two studies from India and Chile reported male predominance [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Another study from Turkey reported 17.6% arthritis and 58.8% arthralgia [13]. Limitations and pain in joints are observed in CNO and arthritis is reported up to 40% in studies [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation